Neurotrophic and antioxidant effects of silymarin comparable to 4-methylcatechol in protection against gentamicin-induced ototoxicity in guinea pigs - Draz, Eman I.; Abdin, Amany A.; Sarhan, Naglaa I.; Gabr, Takwa A. (Pharmacological reports, 2015)
Despite that gentamicin is a very effective aminoglycoside, its potential ototoxicity which is of irreversible nature makes a challenge and limitation for its use. This study was designed to investigate possible neurotrophic and antioxidant effects of silymarin comparable to 4-methylcatechol in protection against gentamicin-induced ototoxicity. Twenty pigmented guinea pigs were divided into four equal groups, where group I served as normal control group. The other groups received gentamicin (120mg/kg/day, ip) for 19 days where group II given vehicle of 1% CMC, group III and group IV were pre-treated 2h before gentamicin by 4-methylcatechol (10μg/kg, ip) and silymarin (100mg/kg, oral gavage), respectively. The main findings indicated that silymarin exhibited restoration of nerve growth factor (NGF) levels and increased tropomyosin-related kinase receptors-A (Trk-A) m-RNA expression in cochlear tissue and preservation of hair cells of organ of Corti by scanning electron microscopy (SEM) with significant decrease in auditory brainstem response (ABR) threshold compared to 4-methylcatechol. Only silymarin caused significant amelioration in oxidative stress state by reducing malondialdehyde (MDA) levels and increasing catalase activity. Silymarin exerts superiority over 4-methylcatechol when recommended as protective agent against gentamicin ototoxicity based on its efficient neurotrophic and antioxidant activities.